Relación entre el estado nutricional y la estimulación ambiental con el rendimiento cognitivo y escolar del niño de primer grado de la zona central media del Perú (costa, sierra y selva) - Majluf, Alegría (1988)
Nutritional status and enviromental stimulation were related to cognitive and academic performance of peruvian 6 year olds from the Coast, Highlands and Jungle regions. 146 low SES children and their mothers, and 50 middle SES children were evaluated. Cognitive and academic performance were highly related. Cronic malnutrition seerned to affect Reading and Mathematical performance. Sociocultural factors affected cognitive development, sex and regional factors had variable effects.